Strategi Digital Marketing untuk Pemasaran Produk UMKM Madu Wana Apis Desa Wonotirto - Achamad Zaenal Abidin; Alviana Maqsurotullaeli; Rizka Ekawati; Njaib Ubaibur Rohman; Astutining Dyah Wulandari; Adila Pinasti; Ahmad Fikri Reswara Maulana Cholil; Alfi Ningamatuzzulfa; Aldin Waly Raihan; Alfina Isnawati; Ilham Akbar Arifin; Rikza Rifqi Alfiyan; Kuspriyadi Kuspriyadi; Sri Hartiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
In the rapidly evolving digital era, digital marketing strategies are crucial for the sustainability and competitiveness of Micro, Small, and Medium Enterprises (MSMEs). This study focuses on the implementation of digital marketing strategies for promoting MSME honey products from Wana Apis in Wonotirto Village, Temanggung Regency. The research employs a qualitative descriptive method through observation, interviews, and document analysis. The findings indicate that utilizing social media, websites, SEO optimization, email marketing, and collaborations with influencers significantly enhance product visibility and sales. Additionally, mentoring MSME actors in product branding, such as logo design and packaging renewal, strengthens product identity in the digital marketplace. By adopting the right strategies, MSME Wana Apis Honey has the potential to compete in an increasingly competitive market and achieve sustainable business growth.